POSTOPRATIVE REHABILITATION PROTOKOL AFTER MPSH / MODIFIED PERCUTANEAL SUTURE / OF ACHILES TENDON. - Martin Barnev; Pavlin Apostolov; Petar Milkov (Peytchinski Publishing, 2012)
We present clinical study of 68 patients / male, mean age 38.5 yr / s applied early loading and functional treatment following percutaneous suture of Achilles tendon. Postoperatively were followed clinically and sonographic 3-6-12 meters of the results defined / visual analog scale / VSA in the score. In all patients, there are normal physical activity without significant differences in the mobility of the ankle joint. Not seen repeated ruptures. We agree that early mobilization and functional treatment did not increase the risk of reruptured and leads to excellent early function parameters of plantar flexione.